2021
DOI: 10.3390/fractalfract5040142
|View full text |Cite
|
Sign up to set email alerts
|

Surface Cracking and Fractal Characteristics of Bending Fractured Polypropylene Fiber-Reinforced Geopolymer Mortar

Abstract: Fiber is effective in restricting cracks and improving the toughness of geopolymer composites, but few studies have focused on the surface crack characteristics of fiber-reinforced geopolymer composites. In this paper, after flexural tests of polypropylene fiber-reinforced geopolymer mortar, the surface cracking image was collected by a digital camera and cracking information was extract by deep learning. Finally, the cracking and fractal characteristics were specifically discussed. The semantic segmentation n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Fractal theory is a new method of mathematics, resolving the irregularities in nature [67][68][69][70]. Many researchers [71][72][73][74][75][76][77][78] demonstrated that fractal theory links microstructures with the macro-performance of cement-based materials well, and vice versa.…”
Section: Fractal Dimension Calculationmentioning
confidence: 99%
“…Fractal theory is a new method of mathematics, resolving the irregularities in nature [67][68][69][70]. Many researchers [71][72][73][74][75][76][77][78] demonstrated that fractal theory links microstructures with the macro-performance of cement-based materials well, and vice versa.…”
Section: Fractal Dimension Calculationmentioning
confidence: 99%
“…They demonstrated that the multiscale hybrid fibers act as a bridging ligament and resist against crack propagation under dynamic load, resulting in a longer time period with improved displacement, strain, and acceleration, and also proposed optimized mixtures for short- and long-length hybrid fibers. Li et al [ 28 ] performed flexural strength tests on polypropylene fiber-reinforced geopolymer mortar. They collected the surface cracking images using a digital camera and extracted cracking information by deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of artificial intelligence, it has been widely used in various engineering fields, such as intelligent transportation, [9][10][11] smart construction sites, [12][13][14] and structural damage monitoring. [14][15][16][17] Artificial intelligence (AI) is a branch of computer science that aims to simulate human intelligence with machines. AI systems use techniques such as machine learning, particularly deep learning, to present ''intelligent'' behavior.…”
Section: Introductionmentioning
confidence: 99%